Transport Equation for Shock Strenght in Hyperelastic Rods - S. Kosiński (Engineering Transactions, 1995)
The singular surface theory and perturbation method of solution are used to examine a 1–D shock wave propagation problem in a semi-infinite rod of slowly varying cross-sectional area. The isentropic approximation is used. The weak nonlinear shock propagates into a region, which is homogeneously deformed and at rest. A numerical analysis for decreasing and increasing cross-sectional areas, and for a special type of nonlinear elastic material is conducted.